Permasalahan Keadaan Dan Hubungan Keluarga ( KHK ) Siswa dan Upaya Guru Bimbingan Konseling dalam Mengatasinya di SMP Negeri 1 Muara Rupit Kabupaten Musi Rawas Utara - Putra, M. Defriansyah Angga; Ristianti, Dina Hajja; Sari, Rini Puspita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
M Defriansyah Angga Putra, NIM 22811003, Problems and Conditions of Students' Families and the Role of Guidance and Counseling Teachers in Overcoming Them at SMP Negeri 1 Muara Rupit, Thesis, Postgraduate Program IAIN Curup, Islamic Education Guidance and Counseling Study Program (BKPI), 2024. 71 pages. The conditions and problems in the family experienced by students will more or less affect the student's personality which is reflected in the student's negative or positive behavior. The problems experienced by these adolescents have different backgrounds. Carrying out negative behavior is due to their unstable condition. To overcome these problems, the school plays an important role in overcoming the problems that occur due to the conditions and problems in the family. In the scope of the school, those who have an important role in helping students overcome their own problems are guidance and counseling teachers. BK teachers have an important role in helping students overcome the problems they face through the services provided by counselors. This research is a qualitative research, using a case study approach where data collection techniques use observation, interviews, and documentation. Based on the results of the study obtained from observations and interviews with homeroom teachers and guidance and counseling teachers for grades VII, VIII, and IX, students who experience problems caused by circumstances and problems in the family caused by several factors, namely economic, poor communication and parental divorce, which affects their behavior to negative behavior. Their negative behaviors include playing truant, rebelling against teachers, or being insecure, seeking attention, being emotional, and fighting. To deal with students like this, each guidance and counseling teacher has their own way of playing a role in overcoming student problems caused by problems in the family. In addition to providing individual guidance services, providing motivation, guidance and counseling teachers will also call parents and make home visits to overcome problems as a whole. In grade VIII, guidance and counseling teachers will provide individual and group counseling services by providing positive reinforcement in the form of support, praise and reinforcement for the plans they make. Meanwhile, for grade IX BK teachers, they provide consultation service guidance, where this service is carried out with the aim that consultation in this case parents have self-ability in the form of insight, understanding, and ways of acting that are directly related to the atmosphere or problems of third parties. Keywords: Guidance and Counseling, Problems and conditions in the family